2010
DOI: 10.1128/aac.00068-10
|View full text |Cite
|
Sign up to set email alerts
|

Development of Hexadecyloxypropyl Tenofovir (CMX157) for Treatment of Infection Caused by Wild-Type and Nucleoside/Nucleotide-Resistant HIV

Abstract: CMX157 is a lipid (1-0-hexadecyloxypropyl) conjugate of the acyclic nucleotide analog tenofovir (TFV) with activity against both wild-type and antiretroviral drug-resistant HIV strains, including multidrug nucleoside/ nucleotide analog-resistant viruses. CMX157 was consistently >300-fold more active than tenofovir against multiple viruses in several different cell systems. CMX157 was active against all major subtypes of HIV-1 and HIV-2 in fresh human peripheral blood mononuclear cells (PBMCs) and against all H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 44 publications
0
45
0
Order By: Relevance
“…In contrast, TFV has EC 50 s against HIV-1 groups M and O that range between 500 and 2,200 nM in peripheral blood mononuclear cells (PBMCs) (24). In an in vitro study, CMX157 demonstrated potent activity against NRTIresistant strains, including multidrug-resistant viruses, against which it showed Ͼ300-fold the activity of TFV (38). The higher potency and lower EC 50 of CMX157 are due to better cellular uptake than that for TFV and the fact that it is not a substrate for organic anion transporters.…”
Section: Newer Nrtismentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, TFV has EC 50 s against HIV-1 groups M and O that range between 500 and 2,200 nM in peripheral blood mononuclear cells (PBMCs) (24). In an in vitro study, CMX157 demonstrated potent activity against NRTIresistant strains, including multidrug-resistant viruses, against which it showed Ͼ300-fold the activity of TFV (38). The higher potency and lower EC 50 of CMX157 are due to better cellular uptake than that for TFV and the fact that it is not a substrate for organic anion transporters.…”
Section: Newer Nrtismentioning
confidence: 99%
“…CMX157 (Fig. 1) is a lipid moiety prodrug of TFV that has activity against wt viruses of major HIV-1 subtypes, with EC 50 s ranging from 0.2 to 7.2 nM (38). In contrast, TFV has EC 50 s against HIV-1 groups M and O that range between 500 and 2,200 nM in peripheral blood mononuclear cells (PBMCs) (24).…”
Section: Newer Nrtismentioning
confidence: 99%
See 1 more Smart Citation
“…Assays involving HIV-1 infection of human peripheral blood mononuclear cells (PBMCs) were performed as described previously (19,34). Fresh PBMCs, seronegative for HIV-1 and hepatitis B virus, were isolated from blood samples of the screened donors (Biological Specialty Corp., Colmar, PA) by using lymphocyte separation medium (density, 1.078 Ϯ 0.002 g/ml; Cellgro; Mediatech, Manassas, VA) and following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Testing of the efficacy of PD against HIV-1 in PBMCs (Biological Specialty Corporation, Colmar, PA) was performed at the Southern Research Institute as described previously (24,25). Briefly, phytohemagglutinin-stimulated cells from at least two healthy donors were mixed together, diluted in fresh medium to a final concentration of 1 ϫ 10 6 cells/ml, and plated in a 96-well round-bottom microplate at 50 l/well (5 ϫ 10 4 cells/well).…”
Section: Cellsmentioning
confidence: 99%